Exile, “de-exile” and “deterritorialization” in Mario Benedetti’s narrative (Revista de Crítica Literaria Latinoamericana, 2013)
This article analyzes Mario Benedetti's narrative work during his period of political exile and his subsequent return to Uruguay. Both, the exile and his return to Uruguay, are seen as a whole. The topics studied in this article are political torture, the heroism of those who were tortured, the consequences of torture, the conflict of returning to Uruguay, as well as the conflict of leaving the country where the exile took place.
Keywords: exile; political repression; deterritorialization; Mario Benedetti